In-vitro Assessment of Antibacterial and Electrochemical Properties of Methanolic Leaf Extracts of Holigarna ferruginea March. The Poisonous Plant Species in the Western Ghats - Manjunath, Kumbar Mudakappa; Krishnamurthy, Yelugere Linganaik (Asian Journal of Biological and Life Sciences)
Background: The Holigarna ferruginea. March. (Black varnish tree) is one of the plant species belonging to the family Anacardiaceae, it is endemic to the Western Ghats. The whole genus shows potent medicinal properties in human life. on that criterion, we took action Aim: To evaluate the antibacterial properties of methanolic leaf extract of Holigarna ferruginea. March. Materials and Methods: The chopped and shade-dried leaves were extracted using Soxhlet and methanol as solvent. Preliminary phytochemical screening revealed the presence of alkaloids, phenols, flavonoids cardiac glycosides, steroids, and tannins. The current research was carried out to investigate the antibacterial activity of Holigarna ferruginea. March. against Both Grampositive and Gram-negative bacteria, pathogens whose many species are responsible for a wide range of diseases. And also studied scavenging properties by an electrochemical method (Cyclic voltagramm). Results: The methanolic leaf extract was tested for antibacterial activity using the well diffusion technique, in which the wells with varying concentrations of the extract were prepared and used. It was at a dosage of 5mg/ml, the methanolic extracts were more effective, with greater inhibition zones in Salmonella enterica (17.66±0.57 mm), Staphylococcus aureus (17.66±0.57 mm), Escherichia coli (17.66±0.57 mm/) and Klebsiella pneumonia (16.66±0.57), then the additional concentrations of 2.5, and 1.25mg/ml were reported comparatively less zone of inhibition in all pathogenic bacteria. From this stud the Holigarna ferruginea. March. had excellent efficacy against both Gram-positive and Gram-negative bacteria. The electrochemical method was evidenced and reported moderate scavenging properties and confirms the presence of free radicals in the extract. Conclusion: These findings suggest that H. ferruginea has antibacterial and antioxidant properties, making it a potentially useful antimicrobial phytomedicine. The reported activity backs up the plant’s traditional use in the treatment of infectious diseases.
Keywords: Antibacterial; Cyclic voltagramm.; GC-MS; Holigarna ferruginea